ANALISIS KEMAMPUAN KEUANGAN DAERAH DALAM MEMBIAYAI PENGELUARAN DAERAH DI KABUPATEN KETAPANG - B61110069, DEVY HARINDA (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT After regional autonomy, local governments have a great opportunity to manaage local financial includes making regional regulationwhich can be changed at any time. These conditions have made high economic costs and local ego in improving its local income. In the implementation in Ketapang regency, the ability to implement regional autonomy is still relatively low in the category of financial viability, and the level of dependence on the central government is still very high in financing development activities, so that the writteris interested to discuss the ability of region financial in defraying the local expending in Ketapang regency, therefore, the writter choses Thesis title